Passively Measuring TCP Round-Trip Times. - STROWES, STEPHEN D. (Communications of the ACM, 2013)
The article explores the measurement of network round-trip time (RTT) using the Transmission Control Protocol (TCP). It discusses the importance of measuring and monitoring RTT, including allowing network operators and end users to understand their network performance and help optimize their environment. The use of the algorithm for calculating RTT by end users is discussed. In addition, the article presents three examples demonstrating bufferbloat: the ability to monitor changing RTT accurately by modifying network; the impact of packet loss; and the impact of oversized buffers.